2019
DOI: 10.1177/1055665619850441
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of American Cleft Palate-Craniofacial Association-Approved Teams’ Websites for Patient-Oriented Content and Readability

Abstract: Objective: Informed decision-making relies on available information, including online resources. We evaluated the content and readability of websites published by American Cleft Palate-Craniofacial Association (ACPA)-approved cleft lip and/or palate (CLP) teams in the United States. Design: Team websites were reviewed, and teams with no accessible website or <30 sentences of content were excluded. Website content was scored by presence/absence of 20 variables derived from ACPA approval standards. Readabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…The FRES and FKGL were used for several reasons, including the ease of calculation, historical comparisons available in the literature, and the documented congruency these metrics have with other tools, such as SMOG or Coleman-Liau Index to measure reading grade level. 14 For CL/P, the average FRES was considered fairly difficult to read (10-12th Grade reading level), and FKGL was considered standard plain English (8-9th Grade reading level). For CFS websites, the average FRES was considered difficult to read (13-16th Grade reading level/College), and FKGL was considered standard plain English (8-9th Grade reading level).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FRES and FKGL were used for several reasons, including the ease of calculation, historical comparisons available in the literature, and the documented congruency these metrics have with other tools, such as SMOG or Coleman-Liau Index to measure reading grade level. 14 For CL/P, the average FRES was considered fairly difficult to read (10-12th Grade reading level), and FKGL was considered standard plain English (8-9th Grade reading level). For CFS websites, the average FRES was considered difficult to read (13-16th Grade reading level/College), and FKGL was considered standard plain English (8-9th Grade reading level).…”
Section: Discussionmentioning
confidence: 99%
“…13 These findings were redemonstrated by Alfonso and colleagues in their 2019 study where they found that the average reading level for the information provided by approved teams listed by the American Cleft Palate-Craniofacial Association was 10.7, and no websites were found to meet the recommended standard of a sixthgrade reading level. 14 Despite promising findings from the most recent literature indicating that "cleft palate surgery" readability is approximately at the seventh-grade reading level, the historical trend for readability studies focuses on cleft care or aggregate craniofacial websites without comparison. 15 The goal of this study was to evaluate the readability of the most popularly searched websites providing parents information related to CL/P and other CFS using validated readability tools to assess whether these websites are adhering to current recommended standards, as well as to explore for differences that may exist between CL/P and CFS websites.…”
Section: Introductionmentioning
confidence: 99%
“…The mean DISCERN score for patient-searched websites was not statistically different from that for physician-recommended websites (3.21 vs 3.62, respectively; P =.16). Numerous studies [ 12 , 13 , 15 - 17 ] identified that readability, as analyzed by the Flesch-Kincaid Tool, of web-based information exceeded the recommended sixth to eighth grade reading levels [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have emphasized the readability, simplicity, and intelligibility of information resources for patients. 20,[25][26][27] Furthermore, in studies such as Ashrafi-Rizi et al, 28 developing credible information content for patient training has been considered one of the common responsibilities of medical librarians and healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%